Real World Evidence: A Quantitative and Qualitative Glance at Participant Feedback from a Free-Response Survey Investigating Experiences of a Structured Exercise Intervention for Men with Prostate Cancer. (3rd July 2017) - Fox, L.; Cahill, F.; Burgess, C.; Peat, N.; Rudman, S.; Kinsella, J.; Cahill, D.; George, G.; Santaolalla, A.; Van Hemelrijck, M.
Abstract : Aim . To explore patient experiences of a structured exercise intervention for men with prostate cancer (PCa). Sample . 41 men with either localised or advanced PCa who had been referred for a structured exercise programme by their physician and then subsequently consented to a telephone survey. Method . Participants underwent a 10-week supervised exercise programme within a large cancer centre hospital consisting of 8 sessions. They then completed a short multiple choice telephone survey, elaborating on their responses where appropriate. Views expressed by participants were analysed using an affinity diagram and common themes were identified. Results . Feedback from our telephone surveys was consistently positive and suggests that the structured exercise intervention provides exercise confidence, motivation to exercise, and social support and promotes positive health behaviour change in the context of exercise. Individual differences arose amongst participants in their perceived utility of the intervention, with 73.3% expressing a preference for structured exercise classes and 19.5% expressing a preference for exercising independently. Conclusion . Design of a structured exercise intervention for patients with PCa should embrace the positive aspects outlined here but consider patients' individual differences. Ongoing feedback from patients should be utilised alongside traditional study designs to inform intervention design in this area.